Cost-effectiveness of paediatric surgery: an economic evaluation of World Paediatric Project surgical interventions in St. Vincent and the Grenadines (2002–2019) - Carrie B Dolan; Justice Nonvignon; Samuel A Agyemang; Brian Clare; Charles Coleman; Bill Richter; Emily Robertson (BMJ Open)
Objectives The purpose of this study is to examine the cost-effectiveness of six types of surgical interventions as part of a sustained paediatric surgical programme in St.Vincent and the Grenadines from 2002 to 2019.Design In this economic model, six paediatric surgical interventions (ophthalmic, orthopaedic, plastic, general, urology, neurosurgery) were compared with no surgery in a deterministic cost-effectiveness model. We assessed health benefits as averted disability-adjusted life-years (DALYs). Costs were included from the programme perspective and measured using standard micro-costing methods. Incremental cost-effectiveness ratios (ICERs) were calculated for each type of surgical intervention. Interventions with ICERs of <50% of gross domestic product (GDP) per capita were considered cost-effective. Costs are reported in 2019 US$. Univariate sensitivity analyses were conducted to assess the effect of uncertainty.Results The average cost per procedure was US$16 685 (range: US$9791.78–US$72 845.76). The cumulative discounted 18-year health impact was 5815 DALYs averted with a cost per DALY averted of US$2622. Most paediatric surgical interventions were cost-effective, yielding cost per DALY estimates less than 50% of GDP per capita of St. Vincent and the Grenadines. When undiscounted, only orthopaedic surgeries had cost per DALY more than 50% GDP per capita. When considering discounting, orthopaedic and urology surgeries exceeded the adopted threshold for cost-effectiveness.Conclusions We found that short-term, recurrent surgical interventions could yield substantial economic benefits in this limited resource setting. This research indicates that investment in paediatric surgical interventions is cost-effective for the majority of specialties. These findings are of clinical significance given the large burden of disease attributable to surgically treatable diseases. This work demonstrates that scaling up dedicated surgical programmes for children is a cost-effective and essential component to improve paediatric health.